Islam and science’s perspectives on the endemic plant Dillenia serrata from South Sulawesi - Aziz, Isna Rasdianah; Auriga, Fitriani; Burhan, Eliazar; Cut Muthiadin; Hajrah (Journal of Islam and Science, 2023)
One of Sulawesi's endemic plants, Dillenia serrata, has numerous uses in the culinary, furniture, and health sectors. Society frequently ignores the lack of knowledge on the use of endemic plants. This study aims to provide the public with information on the endemic plant, D. serrata, from an Islamic and scientific perspective, thus, it can be digested and used as effectively as possible in the future. The approach taken was qualitative, and it involved gathering a variety of pertinent facts and figures about the endemic Sulawesi D. serrata plant through library research. The findings of the studies show that there are several verses in QS Al-An'am verse 99, QS Ar-R'ad verse 4, QS Asy Syu'ara verse 7, and QS Al-An'am verse 141 that demonstrate differences as well as similarities in terms of shape and taste as well as related to the various advantages possessed by the D. serrata plant. In addition, it cautions scientists against breeding and conservation activities, one of which is sharing genetic information from these indigenous species.